Indium Phosphide/Reduced Graphene Oxide Composites as High‐Performance Anodes in Lithium‐Ion Batteries. Issue 21 (22nd August 2018) - Liu, Shuling; Wei, Wei; He, Xiaodong
Abstract: Indium phosphide/reduced graphene oxide (InP/rGO) composites were synthesized successfully through a facile one‐step route at 180 °C. The InP nanoparticles can be anchored uniformly on the surface of rGO nanosheets, forming a stable composite. Moreover, the size and dispersibility of InP nanoparticles can be greatly affected by the added rGO amount. The as‐prepared InP/rGO composites show better electrochemical performance than single‐component rGO nanosheets or InP nanoparticles. But, when the amount of rGO added is 5 mg, the electrochemical performance of InP/rGO composite is optimum. It delivers an initial discharge capacity of 1872 mAh g −1 and the reversible specific discharge capacity can remain at 689 mAh g −1 after 100 cycles at a current density of 100 mA g −1 . Even at a current density of 500 mA g −1, the reversible specific capacity could still reach 500 mAh g −1 . The enhanced electrochemical performances of as‐prepared composites might be attributed to the strong interaction between InP nanoparticles and rGO nanosheets. Abstract : Stick it down : Indium phosphide/reduced graphene oxide (InP/rGO) composites are synthesized by using a one‐step route at 180 °C. The InP nanoparticles can be anchored uniformly on the surface of rGO nanosheets. By adjusting the amount of CTAB, the adhesion rate of redox graphene on the InP surface can be controlled to modify the electrochemical performance. When the current density is 50 mA g −1, the optimal sample discharge specific capacity is stable at 797 mAh g −1 .